Role of Dietary L-Arginine in Poultry Production - Fouad, A.M.; El-Senousey, H.K.; Yang, X.J.; Yao , J.H. (International Journal of Poultry Science, 2012)
As a result of impressive progress that made in economic traits such as body weight gain, feed efficiency and breast yield to meet the demands of consumers, nowadays, poultry became more susceptible to obesity, stressors and less ability to resist the common diseases in commercial farms. L-Arginine (L-Arg) supplementation in poultry diets improves egg production, egg weight, modulates lipid metabolism toward reducing total body fat accumulation to improve meat quality and increases antioxidant defense under normal conditions. Also under stress conditions L-Arg has the ability to alleviate this stress and to normalize the growth performance. Dietary L-Arg supplementation reduces ascites mortality under low ambient temperatures, attenuates the adverse effects of heat stress and high stock density, activates the immune system and enhances its responses to different common diseases in poultry farms. Therefore, L-Arg plays a pivotal role in poultry production.